EFFECTIVENESS OF IMPLEMENTATION OF STANDARD OPERATING PROCEDURE PERFORMANCE ON F & B SERVICE STAFF IN KASAVA RESTAURANT ROYAL SAMAJA VILLAS - I Kadek Putra Sugi Artha; I Wayan Basi Arjana; Ida Ayu Elistyawati (Politeknik Negeri Bali, 2018)
This study focuses on the implementation of standard operating procedures by looking at the operational circumstances that take place within the specified period. The purpose of this study is to determine the effectiveness of the application Standard Operating Procedures on F & B Service Staff at Kasava Restaurant Royal Samaja Villas. This study uses descriptive qualitative method by comparing the percentage value to determine the difference of each indicator so that can be done data presentation to draw conclusion. Data collection method in this research is interview, observation, documentation study, literature study. The results of this study indicate that: (1) The decline in service quality of F & B Service Staff due to employee turnover resulting in standard operating procedures not running effectively, (2) The implementation of Standard Operational Procedures by Royal Samaja Villas management and provide a positive change from the F & B Services Staff, so that the quality of service is improved and the operational implementation which refers to the standard operating procedure is effective again